Perfil lipídico en adultos que acudieron a un Laboratorio Clínico – Trujillo - Rodríguez Ventura, Rosenda Rose Mary (2019)
The purpose of this report was to investigate the "Lipid Profile in adults who attended a Clinical Laboratory - Trujillo"; for which serum levels of Total Cholesterol, HDL Cholesterol, LDL Cholesterol, VLDL Cholesterol and Triglycerides in blood serum of 117 adults were determined by the enzymatic method cholesterol oxidase - peroxidase, subsequently evaluating the results obtained and ordered according to established parameters, obtaining the following results: When relating the lipid profile with: sex, it was found that 2. 56% of men and 3.93% of women presented decreased values, 24.4% of men and 39.323% of women normal values and 12.31% of men and 17.44% of women high values; age, in the range of 60-74 years, 20.51% presented normal values and in the range of 45-59 years the 22.39% high values; weight, in the range of 40-70 Kg, 5.98% presented decreased values and 22.56% normal values, in the range of 71-127 Kg, 27.18% high values; blood pressure, 35.73% were normal and 18.97% normal pressure and high lipid profile. The population under study has an altered lipid profile